KEBIJAKAN EKSEKUTIF REFORMA AGRARIA DALAM PERATURAN PRESIDEN NOMOR 86 TAHUN 2018 - Basuni, Basuni; Ratnawati, Elfrida (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
The Basic Agrarian Law (UPPA) or Law No. 5/1960 was widely praised for having a major impact on Indonesian society, which was responsive and combined elements of communalism and individualism. However, UPPA has unrealized goals that are difficult to deny and most defenses regarding UPPA’s failure point to its normative and ideological nature. The purpose of this paper was to discuss studies on UPPA that focused empirically through the use of theory of public policy implementation by Sabatier dan Mazmanian (1983) related to content variables and policy context and critical implementation theory from researchers who used a bottom-up approach and reviewed the steps of implementing bureaucrats. The research method used in this study was literature study and focused on executive policies, bureaucrats’ steps and the context that covered them. The results showed that executive policy through PP No.86/2018 was not in line with the UPPA decision. The PP was contradictory, wanted to support many variables but was in line with the main objectives of agrarian reform. The implementation of UPPA as a top-down policy required the existence of a dominant actor. Even though the implementing bureaucrats had previously reduced the aim of the law to merely legalizing accounting for land negotiations which operated based on market mechanisms. The increasing number of Indonesian citizens who lived in cities creates increasingly complex land problems, regarding changed in land use and various challenges of sustainable development.Keywords: Public Policy Implementation, Agrarian Reform